Development of Discovery Learning Based Modules in Ecosystem Material for Class X Senior High School/Madrasah Aliyah Students - Tanjung, Miftahul Jannah; Tanjung, Indayana Febriani; Adlini, Miza Nina (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This study aims to develop Discovery Learning Based Modules and to determine the level of feasibility, practicality and effectiveness of the developed modules. This study uses the Research and Development (R&D) research method with the ADDIE model consisting of five stages, namely (Analysis, Design, Development, Implementation, Evaluation). The research subjects were class X MIPA at SMA Negeri 4 Binjai with a total of 25 students. The research instruments were teacher needs analysis, validation sheets to obtain product feasibility data, educator response questionnaires and student questionnaires to obtain product practicality data and learning achievement tests to obtain data on the effectiveness of the products being developed. Based on the results of the study in terms of feasibility, material experts scored 94.28% in the "Very Eligible" category, media experts scored 92.94% in the "Very Eligible" category. Meanwhile, in terms of practicality, from the results of the Biology Teacher's responses, an average proportion of 94.66% was included "Very Practical". In the results of the assessment of students have an average proportion of 89.11% with the criteria "Very Interesting". And in terms of effectiveness, the pretest results averaged 53.6 while the posttest results averaged 80.4. So that the N-gain value is 0.53 with a range of 0.30Ë‚ n Ë‚ 0.70 for the "Medium" mixture. So it was concluded, the Discovery Learning based module that had been developed was stated to be feasible, effective, and practical to use, and could increase activeness in solving problems